STUDI REKOMENDASI PENGGALIAN DITINJAU DARI STRUKTUR BIDANG LEMAH DAN KEKUATAN BATUAN LAVA ANDESIT DI DAERAH GIRIMULYO, KECAMATAN GIRIMULYO, KABUPATEN KULONPROGO, PROPINSI DAERAH ISTIMEWA YOGYAKARTA - Nur Widi Astanto Agus Triheriyadi; Arie Noor Rakhman (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2016)
Andesite mining material needs both for industrial development and may be available by way of mining activities. Girimulya area, District Girimulyo, Kulon Progo has abundant natural resources, among which andesite. This study aims to determine the direction of the excavation recommendation in terms of structure and a weak field strength andesite lava rock. Identifying physical properties and mechanical properties of materials on the excavation carried out as igneous rock andesite lava.Collecting data in the field include: plotting the location of observation; identification of rocks and weathering; data recording and sampling rock geology and weathering. Sampling each location point observations were made in the form of samples disrupted. Research in the laboratory / studio in the form of observational petrology, testing the physical properties of rocks and analysis of compressive strength / UCS. Along with field research and laboratory / studio, also conducted research relevant literature.Andesite in the study area is a product of the old volcanic activity that is part of the Old Andesite Formation. In the field, andesite lava fields have a weak form of fracture. Based on the graphical method Pettifer and Fookes (1994) in terms of the structure of the field is weak and the mining rock mechanics properties including the criteria for Easy Ripping to Very Hard Ripping. If it will be mining should be conducted prior to demolition andesite lava rock. Heavy equipment Bulldozer recommended that the type D6, D7, D8 and D9. Furthermore it can be dug with a backhoe to be loaded and transported.